Strategi Manajemen Sumber Daya Manusia dalam Menciptakan Lingkungan Belajar yang Inovatif - Sari Andini; Dara Avira; Eka Satya; Tengku Darmansah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
In the era of globalisation and rapid technological advancement, education faces increasingly complex challenges, especially in terms of innovative learning development. This study aims to provide human resource management strategies in creating an innovative learning environment amidst the rapid development of education. The method used in this study is a literature study and qualitative analysis of various relevant sources, including journals and scientific articles. The findings show that there are three strategies: developing continuous professionals, integrating technology in the learning process, encouraging collaboration and creativity. This research is expected to provide insights for educational institutions in designing more effective development programme.